The Establishment Of Strategic Program In Research Support Service (SPIRESS) In USM Library - Ahmat, Muhammad Akmal; Misaridin, Shahriza Fadly; Azmi, Noor Adilah; Muhammadan, Lizawati; Basri, Jamilah Hassan; Ghazali, Musa Mohamed; Ismail, Abd Halim; Napiah, Mohd Kamal Mohd; Jaafar, Cik Ramlah Che; Hussain, Husriati; Jan, Noor Azlinda Wan; Ahmad, Rosnani; et al. (2016)
Along with the modernization, Malaysia Higher Learning Institutions (HLIs) have implemented multiple kinds of transformation plans. Currently, there is a comprehensive transformation plan written in Malaysia Education Blueprint 2015-2025 (Higher Education) (MEB) (HE) as a guideline for Higher Learning Institutions (HLIs), Polytechnics and Community Colleges. Hence, the HLIs Libraries or known as Academic Libraries were intangibly pressured to perform new roles and services in order to fulfil the future demands in the rapid pace of Research and Development (R&D) landscape. This paper shares Universiti Sains Malaysia (USM) Library’s experience in developing the new service segments called Strategic Program in Research Support Service (SPiReSS). The introduction of SPiReSS was intended to facilitate students and academicians research activities. Five service segments were introduced namely as Mendeley, Easy-to-Write with Microsoft (MS) Word, Open Access Publication, Google Drive, and Google Scholar. This paper described comprehensively on how the USM Library implement the SPiReSS project especially in terms of developing the service model, enhance the Academic Librarians capabilities, analyzing the participants’ feedback, and explain the types of challenges the Academic Librarians encounter. The SPiReSS project has triggered the interest of HLIs community especially in USM. Due to the remarkable result, the SPiReSS project should create more service segments in order to substantially supporting the research activities in HLIs.